Factores sociales en la calidad de vida de los usuarios adultos mayores del Hospital de Apoyo- Chepén- 2018. - Morales Saravia, Jaidy Karely (2019)
The present research report entitled: The social factors in the quality of life of elderly users of the support hospital-Chepén-2018, is to publicize how social factors in older adults, considering their family and friends as part of their environment. The objective of this study is to determine how family and amical support influences the quality of life of users of the "Friends of Health" Program of the Hospital de Apoyo-Chepén. Having as a research problem: How the family and amical support influences the quality of life of the elderly of the "Friends of Health of the Hospital de Apoyo- Chepén 2018" Program? Regarding the methods used, we have: Inductive, Deductive and Descriptive Method. The following techniques were applied: life history, observation, structured interview, survey and, finally, observation and interview record, questionnaire, photographic record; and the Sample was of 38 people who belong to the "Friends of Health" program of the Hospital de Apoyo-Chepén. In the present investigation, conclusions were reached that 58% of older adults have a positive emotional state, while 55% have good family dynamics but 39% of families feel proud of the older adult user, for improving the quality of life of older adults and improving family and friendships.